The role of context in realization of semantic structure of the text - Nazira Amriddinova (Zien Journals, 2022)
This article deals with the study of the moral-philosophical and mythopoetic understanding of a person, age and life in Mikhail Bulgakov's novel "The Master and Margarita", as well as the concepts of a cultural approach in the poetics of the novel.
Keywords: Writer; literary critic; concept; work